Life Cycle Cost Analysis of Highway Project - Mazuki, Ahmad Izzat Asyraf (Universiti Teknologi PETRONAS, 2017)
Every responsible engineer will care about the quality and cost of a project. An engineer need to make sure every structure that he made will not collapse. In the same time, he need to make sure the cost of the project will not be wasted. So, to get an optimum cost of a project, there must be a way to get a high precision of estimation. The main objective of this study is to identify the alternative proposals and to verify alternatives those can be analyzed by using Life Cycle Cost Analysis (LCCA). The scope of study is focus on highway project. Activities involved are gathering data from highway contractor, calculating the total cost until the highway is finished constructed including all the accessories items, data collection from literature review, compiling data in order to analyze using LCCA rigorous methods for feasible material selection and analyzing data using Microsoft Excel software.